Meconium in the Amniotic Fluid of Pregnancies Complicated by Preterm Premature Rupture of Membranes Is Associated With Early Onset Neonatal Sepsis - Michael J. Kupferminc; Elizabeth Wickstrom; Nam H. Cho; Patricia M. Garcia (Hindawi Limited, 1995)
Objective: This study was to determine the significance of meconium in the amniotic fluid of pregnancies complicated by preterm premature rupture of membranes (PPROM) without labor.